Association between triglyceride-glucose index and all-cause mortality in non-diabetic patients with fibrotic lung disease receiving antifibrotic therapy: A retrospective cohort study - Aysegul Erinc; Ali Kirac; Fatma Ezgi Altun Acar; Abdullah Cagri Onal; Erdogan Cetinkaya (PLOS One, 2026)
Introduction Fibrotic lung diseases are associated with significant morbidity and mortality, with a rising prevalence. Prognostic indicators for these diseases include thoracic computed tomography (CT) findings and pulmonary function test (PFT) measures. The triglyceride-glucose (TyG) index, a fasting triglyceride- and glucose-derived surrogate marker of insulin resistance, has been associated with several clinical outcomes; however, its relationship with pulmonary function and all-cause mortality within the non-diabetic range in patients with fibrotic lung disease remains inadequately studied. This study aimed to investigate the association between variability in the TyG index within the non-diabetic range, baseline pulmonary function measures, and all-cause mortality in patients with fibrotic lung disease receiving antifibrotic therapy. Methods This retrospective cohort study was conducted on 144 patients with fibrotic lung disease who received antifibrotic therapy between 1 January 2015 and 1 June 2023. Demographic data, comorbidities, smoking status, PFT measures, fasting glucose, triglyceride levels, and survival data were collected. The TyG index was calculated using the formula: Ln [(fasting triglycerides (mg/dL) × fasting glucose (mg/dL)) / 2]. Survival time was calculated from initiation of antifibrotic therapy to death from any cause or last clinical follow-up, with a median follow-up duration of 33.8 months. Results The mean age of the cohort was 67.4 years, and 31.9% of the patients were female. The mean TyG index was 8.78. During follow-up, 54 of 144 patients (37.5%) died. In the multivariable Cox regression analysis, the TyG index was not significantly associated with all-cause mortality (adjusted HR = 0.80, 95% CI: 0.40–1.60, p = 0.54). Lower FVC% and greater cumulative smoking exposure were associated with all-cause mortality in the adjusted model. Conclusions In this selected cohort of non-diabetic patients with fibrotic lung disease receiving antifibrotic therapy, the TyG index was not significantly associated with all-cause mortality. No consistent association with baseline pulmonary function measures was observed, apart from a weak exploratory inverse correlation with DLCO. However, the restricted metabolic variability and limited statistical precision of the cohort may have reduced the ability to detect modest but potentially clinically meaningful associations. Further prospective studies are needed to clarify the potential prognostic relevance of the TyG index in broader fibrotic lung disease populations.